Creativity: Promotion of the Creative Process; Innovative and Collaborative 21st Century Learning - Eny Winaryati; Muhammad Munsarif; Mardiana Mardiana; Suwahono Suwahono (Budapest International Research and Critics University, 2021)
21st century learning requires the world of education to produce graduates who have creativity, who encourage creative and collaborative processes in solving problems. The purpose of this study was to obtain dimensional data and indicators of creativity skills in students, teachers and school principals. This research method is Mixed Method, with Exploratory Sequential Design model. The conclusions of this study are: (1) The number and names of the dimensions remain the same, namely there are 5 (five) with 21 (twenty one) indicators. (2) There is a change in the number and name of the indicator. The number of indicators for each dimension are: (a) Dimensions of creative thinking ability, there are 4 (four) indicators; (b) Dimensions of working creatively with other people have 3 (three) indicators; (c) There are 6 (six) indicators to interpret a failure; (d) Dimensions of implementing idea innovation into innovation for success, there are 5 (five) indicators; (e) Dimensions of thinking outside the habit there are 3 indicators. Suggestion: Research can be followed up by using dimensions and indicators of 21st century learning creativity skills in students and teachers, with various sample characteristics. The results of the assessment can be used to measure the level of existing creativity skills.